Pengaruh Social Media Usage dan Electronic Word of Mouth terhadap Keputusan Pembelian Online iPhone melalui Trust pada Generasi Z di Kota Semarang - Zahra Aulliya Junianti; Wahyu Setiawan (Lembaga Yasin AlSys, 2026)
The development of social media and the increasing accessibility of digital information have transformed consumer purchasing decision patterns, particularly among Generation Z. This study aimed to analyze the effect of social media usage and electronic word of mouth (e-WOM) on online purchase decisions for iPhone products, with trust as a mediating variable among Generation Z in Semarang City. The research employed a quantitative approach with an accidental sampling technique involving 100 Generation Z respondents who use iPhones. Data were collected through a structured questionnaire and analyzed using the Partial Least Squares (PLS) method with the assistance of SmartPLS 3.0. The results showed that social media usage and e-WOM have a positive and significant effect on trust and purchase decisions, while trust also has a positive and significant effect on purchase decisions. Further findings indicate that trust functions as a significant mediating variable in the relationship between social media usage and e-WOM and online purchase decisions. In conclusion, consumer trust is a key factor that strengthens the influence of social media and online reviews on online purchase decisions for iPhone products among Generation Z. The implications of this study provide a basis for companies to design digital marketing strategies that focus on enhancing information credibility and reinforcing consumer trust, particularly in the Generation Z segment.